2017
DOI: 10.1175/jtech-d-15-0246.1
|View full text |Cite
|
Sign up to set email alerts
|

Ice Crystal Sizes in High Ice Water Content Clouds. Part II: Statistics of Mass Diameter Percentiles in Tropical Convection Observed during the HAIC/HIWC Project

Abstract: High ice water content (IWC) regions in mesoscale convective systems (MCSs) are a potential threat to commercial aviation, as they are suspected to cause in-service engine power-loss events and air data probe malfunctions. To investigate this, the high-altitude ice crystals (HAIC)/high ice water content (HIWC) projects set up a first field campaign in Darwin (Australia) in 2014. The airborne instrumentation was selected to provide the most accurate measurements of both the bulk total water content (TWC), using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 56 publications
9
70
0
Order By: Relevance
“…Ice water content values are smaller, typically 0.01-0.03 g m −3 . Heymsfield et al (2002) reported high ice water content values ranging from 0.1 to 0.5 g m −3 in tropical cirrus and stratiform precipitating clouds, although values rarely reach as high as 1.5 g m −3 in deep tropical convective clouds (Leroy et al, 2017).…”
Section: Cosmic Tpw Productsmentioning
confidence: 99%
“…Ice water content values are smaller, typically 0.01-0.03 g m −3 . Heymsfield et al (2002) reported high ice water content values ranging from 0.1 to 0.5 g m −3 in tropical cirrus and stratiform precipitating clouds, although values rarely reach as high as 1.5 g m −3 in deep tropical convective clouds (Leroy et al, 2017).…”
Section: Cosmic Tpw Productsmentioning
confidence: 99%
“…The dataset includes more than 17 000 data points where all parameters are synchronized and averaged over 5 s. As one of the priority of the HAIC/HIWC projects was to measure high ice water content and the variability of CWC as a function of distance from the convective cores at typical altitudes flown by commercial aircraft, the flight strategy was to fly long legs at constant altitude at −50, −40, −30, and −10 • C and to get as close as possible to the most convective zone of the MCS (see Fig. 2 in Leroy et al, 2017), thereby avoiding red aircraft radar echoes at normal gain as commercial aircraft would also do. More details on HAIC/HIWC projects and implemented flight strategy can be found in Dezitter et al (2013), Leroy et al (2016Leroy et al ( , 2017, Protat et al (2016), and .…”
Section: Data Processingmentioning
confidence: 99%
“…2 in Leroy et al, 2017), thereby avoiding red aircraft radar echoes at normal gain as commercial aircraft would also do. More details on HAIC/HIWC projects and implemented flight strategy can be found in Dezitter et al (2013), Leroy et al (2016Leroy et al ( , 2017, Protat et al (2016), and .…”
Section: Data Processingmentioning
confidence: 99%
“…In particular, mass-size distributions (MSDs) constructed from these measurements may be compared with simulated MSDs in microphysics schemes. L16 and Leroy et al (2017) (hereafter referenced as L17) perform extensive analyses on median mass diameters (MMDs) retrieved from HAIC-HIWC data, a characteristic size metric that provides the diameter at which half of the bulk mass resides in smaller diameters and half resides in larger diameters. By comparing hydrometeor sizes and investigating the model parameters and processes that control size distributions, possible sources for biases may be identified and further observational constraints on these parameters may be implemented.…”
Section: Introductionmentioning
confidence: 99%